2022
DOI: 10.1101/2022.01.21.477255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Energetic decoupling of phycobilisomes from photosystem II involved in nonphotochemical quenching in red algae

Abstract: To mitigate photodamage under fluctuating light conditions, photosynthetic organisms respond by regulating light energy absorbed by light-harvesting complexes and used for photochemistry. Nonphotochemical quenching acts as a frontline response to prevent excitation energy from reaching the photochemical reaction center of photosystem II. The mechanisms underlying nonphotochemical quenching in red algae, which display unique combination of light-harvesting transmembrane antenna proteins and membrane-attached ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Moreover, Lu-Ning Liu et al [ 34 ], working on the unicellular red algae Porphyridium cruentum , proposed another photoprotection mechanism in phycobilisomes involving a light-induced phycoerythrin decoupling as a strategy to block the transfer from phycoerythrin to phycocyanin . Yu-Hao Chiang et al [ 35 ] suggested that the decoupling of the phycobilisome of photosystem II was the dominant process involved in non-photochemical quenching through conformational changes in the extremophilic red alga Cyanidioschyzon merolae .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lu-Ning Liu et al [ 34 ], working on the unicellular red algae Porphyridium cruentum , proposed another photoprotection mechanism in phycobilisomes involving a light-induced phycoerythrin decoupling as a strategy to block the transfer from phycoerythrin to phycocyanin . Yu-Hao Chiang et al [ 35 ] suggested that the decoupling of the phycobilisome of photosystem II was the dominant process involved in non-photochemical quenching through conformational changes in the extremophilic red alga Cyanidioschyzon merolae .…”
Section: Introductionmentioning
confidence: 99%